Suppression of alcohol self-administration and reinstatement of alcohol seeking by melanin-concentrating hormone receptor 1 (MCH1-R) antagonism in Wistar rats - Cippitelli, Andrea; Karlsson, Camilla; Shaw, Janice L.; Thorsell, Annika; Gehlert, Donald R.; Heilig, Markus (Psychopharmacologia, 2010)
Rationale Melanin-concentrating hormone (MCH) is involved in regulation of appetitive behaviors as well as emotional reactivity and reward, behavioral domains relevant to alcohol addiction. Materials and methods We evaluated the effects of the non-peptide MCH1 receptor antagonist, GW803430 [6-(4-chloro-phenyl)-3-[3-methoxy-4-(2-pyrrolidin-1-yl-ethoxy)-phenyl]-3 H -thieno[3,2- d ]pyrimidin-4-one; 3–30 mg/kg, i.p.] on alcohol-related behaviors in Wistar rats. Results Ex vivo binding experiments demonstrated that the GW803430 dose range used resulted in high central MCH1 receptor occupancy. Alcohol self-administration was dose-dependently and potently suppressed, by approximately 80% at the highest dose. Reinstatement of alcohol-seeking induced by alcohol-associated cues was essentially eliminated. In contrast, reinstatement induced by footshock stress was not significantly altered. Taste preference for a quinine/saccharin solution, locomotor activity, and alcohol elimination were unaffected. Conclusion Together, these observations support a specific involvement of the MCH system in mediating alcohol reward and cue-induced relapse to alcohol seeking. MCH1-R antagonism may constitute an attractive treatment target for alcohol use disorders.